PENINGKATAN SELF EFFICACY IBU MELALUI METODE CHALK AND TALK TENTANG PENANGANAN PERTAMA KEJANG DEMAM PADA BALITA DI DESA PLOSOWAHYU KABUPATEN LAMONGAN - Juanita, Farida; Manggarwati, Selviana (Journal of Health Sciences, 2016)
Febrile convulsion is a transient disorder that occurs in some children with fever. Mother’s self-efficacy is determined by her readiness and perseverance in facing a certain situation. The objective of this research is to analyze the effect of the Chalk and Talk methods to improve mother’s self-efficacy about first handling of toddler’s febrile seizure. This research method was using one group pretest-posttest design, with total sampling of 21 subjects, whom have toddlers in the Plosowahyu village Lamongan in February 2016. The data was taken by using questionnaire sheet. Data analyzed by Wilcoxon sign test with p= 0,05. The result of statistical test shows that there is correlation between Chalk and Talk methods of the toddlers’ febrile seizure handling with the mothers’ self-efficacy. The correlation coefficient value is -3,852 with level of significant 0,000 (p<0,05). This research show that Chalk and Talk methods can improve mothers’ self-efficacy of the first handling toddlers’ febrile seizure. Thus, the health education (trough Chalk and Talk methods) effectively influenced the mothers’ self-efficacy improvement because it could explain the idea and the message, and it also became the reminder of what the presenter had explained.> <0,05). This research show that Chalk and Talk methods can improve mothers’ self-efficacy of the first handling toddlers’ febrile seizure. Thus, the health education (trough Chalk and Talk methods) effectively influenced the mothers’ self-efficacy improvement because it could explain the idea and the message, and it also became the reminder of what the presenter had explained.